2022
DOI: 10.5935/1984-0063.20220021
|View full text |Cite
|
Sign up to set email alerts
|

Quality of sleep in women with menopause and its related factors

Abstract: Background: Menopausal period is one of the most critical stages of a womans life. Complications of the menopausal period including sleep disorders can affect the physical and mental state of women. As sleep disorder has a determinant role in the quality of life, this study was conducted to evaluate postmenopausal womens quality of sleep and its related factors. Material and methods: This cross-sectional-analytical study was conducted on 323 postmenopausal women based on convenience and consecutive sampling. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…This perception may hinder timely interventions and exacerbate the impact of sleep disorders on overall well-being. To address this attitude, interventions should target misconceptions about the normalcy of sleep disorders during perimenopause 29 , 30 . Educational campaigns can incorporate narratives from individuals who have successfully managed sleep issues during this life stage, emphasizing the benefits of seeking professional guidance.…”
Section: Discussionmentioning
confidence: 99%
“…This perception may hinder timely interventions and exacerbate the impact of sleep disorders on overall well-being. To address this attitude, interventions should target misconceptions about the normalcy of sleep disorders during perimenopause 29 , 30 . Educational campaigns can incorporate narratives from individuals who have successfully managed sleep issues during this life stage, emphasizing the benefits of seeking professional guidance.…”
Section: Discussionmentioning
confidence: 99%
“…Subjective sleep quality, which encompasses waking after sleep onset, number of awakenings, sleep latency, and sleep efficiency, has been reported to decline in a linear fashion with increasing age. 1 , 4 , 5 , 9 , 10 , 11 , 12 Postmenopausal women are more likely to report sleep disorders than their premenopausal counterparts and among postmenopausal women, those with surgically induced menopause have worse sleep quality than those with naturally occurring menopause. 1 , 4 , 13 , 14 Data on the impact of hormone therapy (HT) on sleep quality during the menopausal transition are conflicting.…”
Section: Background and Aimsmentioning
confidence: 99%
“…In animal and in vitro studies, oestrogen was found to play several neuroprotective roles including promoting survival of cholinergic neurons, metabolism of APP through the non-amyloidogenic pathway, and via antioxidant properties [53]. Hormonal changes experienced in menopause can result in altered sleeping patterns [54] and cognitive dysfunction [55]. Individually, these symptoms are risk factors for AD, but in combination with decreasing oestrogen, they may explain why women are at a higher risk of developing the disease than men [50,52].…”
Section: Non-modifiable Risk Factorsmentioning
confidence: 99%